Activity of the α-glucoside transporter Agt1 in Saccharomyces cerevisiae cells during dehydration-rehydration events. Issue 6 (June 2018) - Kulikova-Borovikova, Diana; Lisi, Silvia; Dauss, Edgars; Alamae, Tiina; Buzzini, Pietro; Hallsworth, John E.; Rapoport, Alexander
Abstract: Microbial cells can enter a state of anhydrobiosis under desiccating conditions. One of the main determinants of viability during dehydration-rehydration cycles is structural integrity of the plasma membrane. Whereas much is known about phase transitions of the lipid bilayer, there is a paucity of information on changes in activity of plasma membrane proteins during dehydration-rehydration events. We selected the α-glucoside transporter Agt1 to gain insights into stress mechanisms/responses and ecophysiology during anhydrobiosis. As intracellular water content of S. cerevisiae strain 14 (a strain with moderate tolerance to dehydration-rehydration) was reduced to 1.5 g water/g dry weight, the activity of the Agt1 transporter decreased by 10–15 %. This indicates that functionality of this trans-membrane and relatively hydrophobic protein depends on water. Notably, however, levels of cell viability were retained. Prior incubation in the stress protectant xylitol increased stability of the plasma membrane but not Agt1. Studies were carried out using a comparator yeast which was highly resistant to dehydration-rehydration ( S. cerevisiae strain 77). By contrast to S. cerevisiae strain 14, there was no significant reduction of Agt1 activity in S. cerevisiae strain 77 cells. These findings have implications for the ecophysiology of S. cerevisiae strains in natural and industrial systems. Graphical abstract: Highlights: Functional activity of plasma membrane protein Agt1 at yeast dehydration was tested. First changes of Agt1 activity took place at the beginning of water elimination. Treatment of yeast in xylitol solutions had no protective effect upon Agt1 protein. Plasma membrane proteins stability is linked to strain resistance at dehydration.